Evaluation of cow pat pit as a component of integrated nutrient management for rice (Oryza sativa)-wheat (Triticum aestivum) cropping sequence - Dhyani, B P; Shahi, U P; Baliyan, Vikas; Kumar, Yogesh; Singh, R R; Kumar, Ashok; Singh, S P; Ram, B; Yadav, R B (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2004-06 to evaluate cow pat pit as a component of integrated plant nutrient management in rice (Oryza sativa L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping sequence at Crop Research Centre of the University, Meerut in a sandy loam soil. Fourteen different treatments were tested in a randomized block design. Result revealed that neither the application of Azotobacter or phosphorus-solubilizing bacteria nor cow pat pit with 75% NPK were able to substitute 25% NPK requirement of rice and wheat but when 75% NPK and cow pat pit were applied either with Azotobacter or solubilizing bacteria the substitution of 25% NPK was possible. Organic carbon, available phosphorus and potassium were affected significantly due to different treatments while pH and bulk density remained unaffected.